Diversification in Functions and Expressions of Soybean FLOWERING LOCUS T Genes Fine-Tunes Seasonal Flowering - Lee, Su Hyeon; Choi, Cheol Woo; Park, Kyoung Mi; Jung, Wook-Hun; Chun, Hyun Jin; Baek, Dongwon; Cho, Hyun Min; Jin, Byung Jun; Park, Mi Suk; No, Dong Hyeon; Lim, Lack Hyeon; Shim, Sang In; et al. (Frontiers in Plant Science, 2021)
The proper timing of flowering in response to environmental changes is critical for ensuring crop yields. FLOWERING LOCUS T (FT) homologs of the phosphatidylethanolamine-binding protein family play important roles as floral integrators in many crops. In soybean, we identified 17 genes of this family, and characterized biological functions in flowering for ten FT homologs. Overexpression of GmFT homologs in Arabidopsis revealed that a set of GmFT homologs, including GmFT2a/2b, GmFT3a/3b, and GmFT5a/5b, promoted flowering similar to FT; in contrast, GmFT1a/1b, GmFT4, and GmFT6 delayed flowering. Consistently, expressions of GmFT2a, GmFT2b, and GmFT5a were induced in soybean leaves in response to floral inductive short days, whereas expressions of GmFT1a and GmFT4 were induced in response to long days. Exon swapping analysis between floral activator GmFT2a and floral repressor GmFT4 revealed that the segment B region in the fourth exon is critical for their antagonistic functions. Finally, expression analysis of GmFT2a, GmFT5a, and GmFT4 in soybean accessions exhibiting various flowering times indicated that the mRNA levels of GmFT2a and GmFT5a were higher in early flowering accessions than in late-flowering accessions, while GmFT4 showed the opposite pattern. Moreover, the relative mRNA levels between GmFT2a/GmFT5a and GmFT4 was important in determining day length-dependent flowering in soybean accessions. Taken together, our results suggest that the functions of GmFT homologs have diversified into floral activators and floral repressors during soybean evolution, and the timing of flowering in response to changing day length is determined by modulating the activities of antagonistic GmFT homologs.